PELATIHAN KOMPETENSI KEWIRAUSAHAAN PADA UKM - Hidayah, Nur; Avisca , Gemitalia (Transpublika Publisher, 2021)
Competence plays a crucial role in ensuring the sustainability of a business. The success of a business is often attributed to its ability to enhance the competence of its operations. The purpose of the PKM activities is to assist small and medium-sized enterprises (SMEs) in recognizing the significance of entrepreneurial competence in sustaining their businesses. The activity partners involved in this study are engaged in the culinary industry, specifically under the brand name